A comparison of complete mitochondrial DNA sequences of Mnais costalis Selys, 1869 (Odonata: Calopterygidae) from three different populations (one allopatric and two sympatric). Issue 2 (3rd July 2019) - Okuyama, Hisashi; Kiyoshi, Takuya; Takahashi, Jun-Ichi; Tsubaki, Yoshitaka
Abstract: In Japan, two closely-related damselflies, Mnais costalis Selys, 1869 (Odonata: Calopterygidae) and M. pruinosa Selys-Longchamps (Odonata: Calopterygidae), 1853, coexist, and they exhibit geographic variations in wing color, body size, and habitat preference. In this study, we analyzed the complete mitochondrial genome of M. costalis from Saga Prefecture, Japan (sympatric populations that exhibit wing color polymorphism), and compared the genome with M. costalis that exhibit monomorphic orange wing color. The mitochondrial genome of M. costalis from Saga Prefecture was identified as a circular molecule of 15, 488 bp, similar to that found in other M. costalis populations. It was predicted to contain 13 protein-coding (PCG), 22 tRNA, and two rRNA genes, along with one A + T-rich control region. Among the PCGs, ATP8 and ATP6, ATP6 and COIII, ND4 and ND4L, and ND6 and Cytb shared seven, one, seven, and one nucleotides, respectively. The initiation codon ATG was found in eight genes, ATC in four, and ATT in one, while the termination codons TAA, TAG, TA, and T were observed in seven, one, two, and three genes, respectively. All the tRNA genes possessed a cloverleaf secondary structure, except for tRNA-His that lacks the TΨC loop. The average AT content of mitochondrial genome was 66.06%. From a phylogenetic analysis, the loss of wing color polymorphism in monomorphic sympatric populations is likely to occur with the coexistence of two Mnais species.